The Aryl Sulfide Synthesis via Sulfide Transfer. Issue 35 (11th May 2022) - Liang, Xinyu; Wen, Kaikai; Shi, Qinqin; Zhang, Bei‐Bei; Pei, Shurui; Lin, Qijie; Ma, Bowei; Wang, Song; Zhang, Meng; Li, Xiang; Wang, Zhi‐Xiang; Huang, Hui
Abstract: Aryl sulfides are in great demands in drugs and materials sciences. To avoid using nucleophilic and noxious thiols, many efforts have been focused on exploring novel sulfide resources. Herein, a reductive Pd‐catalyzed, Ni‐mediated method to synthesize aryl sulfides via a sulfide transfer reaction is developed. The utility and scope of this reaction is exemplified by various aryl electrophiles and aryl sulfides. Mechanistic studies reveal two competing catalytic cycles of sulfide transfer and aryl transfer in this reaction, where the former one is favored over the later one because of the large energy barrier difference during the transmetalation. Moreover, two important chemicals are late‐stage functionalized by this method, exhibiting the potential applications in drugs and materials science. Abstract : An eco‐friendly sulfide transfer protocol is explored under a reductive Pd‐catalyzed, Ni‐mediated condition. Both experimental and theoretical results support the sulfide transfer over the aryl transfer. Late‐functionalization of drugs and semiconducting materials highlight the importance of the method.